Building the multitasking brain: An integrated perspective on functional brain activation during task-switching and dual-tasking. (September 2019) - Ward, Nathan; Hussey, Erika K.; Cunningham, Emily C.; Paul, Erick J.; McWilliams, Thomas; Kramer, Arthur F.
Abstract: Multitasking behavior is associated with well-known performance costs, but the question of why individuals falter when attempting to manage multiple streams of information remains difficult to answer. One reason for this difficulty may be that multitasking costs are often characterized by isolating component processes that are studied largely independently. In this study, we instead integrate two commonly studied substrates of multitasking, task-switching and dual-tasking, within the same procedural context. This method allows not only a direct comparison of performance costs associated with different demand types but also examination of their interaction. We measured functional brain activation in thirty healthy young adults as they completed a block-design version of the task, observing consistent and separable patterns of frontoparietal activation as a function of demand type. Broadly, task-switching was associated with activation of left premotor and inferior parietal regions, and dual-tasking was associated with activation in regions of right prefrontal and inferior parietal cortex. In the interaction condition, we observed a distributed bilateral pattern of activation across the areas associated with each demand in isolation. These results provide both behavioral and neuroimaging evidence that task-switching and dual-tasking demands can be dissociated and contribute to multitasking costs in unique and separable ways. Highlights: We manipulated task-switching and dual-tasking within a fully-crossed paradigm. Dual-tasking led to slower response times compared to task-switching. Dual-tasking activated primarily right frontoparietal regions. Task-switching activated primarily left frontoparietal regions. Combining demands did not lead to additive behavioral effects.